(untitled) (Annals of Medical Research, 2021)
Aim: Purpose of the study is to determine the magnitude of patient satisfaction with nursing care in tertiary care hospital of Peshawar. Materials and Methods: A cross-sectional descriptive study was conducted in inpatients’ department of tertiary care hospital of Peshawar. Using non probability convenient sampling technique patients were sampled. Study was completed in six months duration. Data was collected through Patient Satisfaction with Nursing Care Scale (PSNCS); self administered semi-structured questionnaire from patients aged 20 and above and who had spent at least two days receiving nursing care in wards. Data was analyzed by SPSS version 19. Results: The level of patients’ satisfaction measured with ten dimensions. Findings showed that satisfaction rate by warm welcome of nurses was 67.8%, orientation from ward environment was 75.5%, and work collaboration of nurses was 92.8%, in care provision, to provide prior information regarding any procedure was 82%, in collaborative communication was 89.9%, in unavoidable attitude and listening were 92.1%, nurses knowledge and skill and performance was 84.2%. Conclusion: Overall study results showed that patients were satisfied from nursing care they received but some aspects i.e. welcome by nurses and environment of ward still need improvement. Patients feel uncertain about their upcoming tests and treatment by health care provider so study suggests that nurses should welcome them warmly and ward environment should be clean, calm and friendly which can help in decreasing patients’ uncertainty.